The Influence of Halal Certification (Self-Declaration) on the Purchase Intention of MSME Food Products in Bandung - Alim, Abdullah; Aziz, Fauzan (Dinasti Publisher, 2024)
The halal product market has garnered significant attention worldwide. Consumers are increasingly cognizant of the importance of selecting products that adhere to the halal principles of the Islamic faith. Halal certification plays a critical role in bolstering consumer confidence in a product. This study aims to explore the influence of halal certification on the purchase intention of Micro, Small, and Medium Enterprises (MSMEs) food products in Bandung. Specifically, it examines the impact of self-declared halal certification on consumers' purchasing decisions. The research sample comprised 100 respondents, and data analysis included validity and reliability tests, data normality tests, correlation analysis, simple linear regression analysis, and the coefficient of determination, utilizing the SPSS program. The findings indicate that self-declared halal certification has a positive and significant effect on the purchase intention of MSME food products in Bandung. This is evidenced by a t-value of 19.408 and a p-value (Sig) of 0.000, which is below the 5% alpha threshold, thereby confirming the research hypothesis.